Penggunaan Platform Digital Pada Pembelajaran Pendidikan Agama Kristen di Era Disrupsi - Priskila Issak Benyamin; Ucok P. Sinaga; Febie Yolla Gracia (Regula Fidei: Jurnal Pendidikan Agama Kristen, 2021)
The era of disruption has had a major impact and influence on the entire learning system of Christian Religious Education (PAK), so that schools and teachers are required to follow this change in the learning system. Even learning in schools is no longer carried out directly but virtual (online) to the influence caused by the era of disruption through platforms that support the learning process. Therefore, in this study, the researcher aims to describe the use of digital platforms in PAK learning in the ERA of disruption. By using a qualitative approach, literature review and literature study by analyzing, then suggesting a PAK learning in the era of disruption. The sources that are prioritized are analyzing including the results of research contained in literature study journals and observing those in accordance with the title of writing. The results of the study of the era of disruption and the use of digital platforms for learning will have an impact on PAK learning, so the author will adjust this phenomenon to what should be done by teachers or education that follows the times in the era of disruption. Abstrak Era disrupsi memberikan dampak dan pengaruh besar kepada seluruh sistem pembelajaran Pendidikan Agama Kristen (PAK), sehingga sekolah maupun guru dituntut untuk mengikuti perubahan sistem pembelajaran ini. Pembelajaran di sekolah tidak lagi dilakukan secara langsung melainkan secara maya (online). Hal ini menuntut untuk penggunaan platform-platform digital yang dapat mendukung proses pembelajaran berjalan dengan baik. Oleh sebab itu, penelitian ini bertujuan mendeskripsikan penggunaan platform digital pada pembelajaran PAK di ERA disrupsi. Untuk mengungkapkan tujuan ini, maka peneliti menggunakan pendekatan kualitatif, dan studi pustaka dengan menganalisis, kemudian mengemukakan sebuah pembelajaran PAK di era disrupsi. Hasil kajian didapati bahwa penggunaan platform digital yang tepat untuk pembelajaran akan berdampak kepada efektivitas dan berjalan lancarnya proses belajar mengajar PAK